2014
DOI: 10.1039/c2sm27207e
|View full text |Cite
|
Sign up to set email alerts
|

Breathing, crawling, budding, and splitting of a liquid droplet under laser heating

Abstract: The manipulation of droplets with sizes on the millimetre scale and below has attracted considerable attention over the past few decades for applications in microfluidics, biology, and chemistry. In this paper, we report the response of an oil droplet floating in an aqueous solution to local laser heating. Depending on the laser power, distinct dynamic transitions of the shape and motion of the droplet are observed, namely, breathing, crawling, budding, and splitting. We found that the selection of the dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…Alternatively, because the surface tension of liquids is temperature-dependent, the position of a liquid droplet can be manipulated by generating a surface tension gradient across the droplet via localized heating. 4,5 Additionally, flow transport within small geometries such as pores and microchannels can be greatly affected by surface energy. In crude oil recovery, for example, the rate of oil extraction from subterranean reservoirs is strongly affected by surface energy in combinatory interactions between oil and surrounding porous media such as soil and rock.…”
mentioning
confidence: 99%
“…Alternatively, because the surface tension of liquids is temperature-dependent, the position of a liquid droplet can be manipulated by generating a surface tension gradient across the droplet via localized heating. 4,5 Additionally, flow transport within small geometries such as pores and microchannels can be greatly affected by surface energy. In crude oil recovery, for example, the rate of oil extraction from subterranean reservoirs is strongly affected by surface energy in combinatory interactions between oil and surrounding porous media such as soil and rock.…”
mentioning
confidence: 99%
“…While some non-stationary phenomena were formerly observed in droplets under laser heating (Rybalko et al 2004;Song et al 2014) A.1. Original boundary value problem For the sake of simplicity, on the first stage we disregard the gravity and the disjoining pressures.…”
Section: Discussionmentioning
confidence: 97%
“…The direction of motion can be different depending on the details of the generated convective flow (Rybalko, Magome & Yoshikawa 2004) and the droplet shape (Yakshi-Tafti, Cho & Kumar 2010). Moreover, by the laser heating of a droplet, the direction of motion can change periodically with time (Rybalko et al 2004;Song et al 2014). Let us mention also experiments on droplet evaporation where the buoyancy-thermocapillary convection caused by the evaporative cooling creates hydrothermal waves (Buffone 2019) and leads to the droplet disintegration (Keiser et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Various kinds of droplet division and other behavior modes (explosion, vibration, stardust, galaxies) were observed by Croninʼs group when searching the compositional space of the droplets placed in an aqueous phase [43]. Song et al [87] have shown the splitting of droplets by laser irradiation. It is notable that in [43] the behaviors of droplets were selected over time, resulting in the evolution of droplet composition.…”
Section: Droplet Divisionmentioning
confidence: 99%